The Seedlings Growth Performance of Areca Nut Palm (Areca catechu L.) under Different Types of Organic Mulching - Siska Syaranamual; Donatus Sipyan; Veronica Leonora Tuhumena; Inna Martha Rumainum; Dwiana Wasgito Purnomo (Universitas Sebelas Maret, 2022)
Seedlings is the initial part of seed plant’s growth and development including areca nut palm which germination is an essential part of it. Organic mulching is one of the utmost sustainable practices, therefore, it has been employed to enhance areca nut seedlings growth. The study aims to evaluate the effect of several types of organic mulch on areca nut seedlings shoot-root growth. The 3-month long experiment was conducted according to completely randomized design, with four treatments, namely no mulching (control) (M0), gliricidia (Gliricidia sepium) mulching (M1), imperata (Imperata cylindrica) mulching (M2) and lamtoro (Leucaena leucocephala) mulching (M3). The treatments were repeated 5 times with 20 experimental units. The findings revealed that no significant differences (p < 0.05) were found on the application of different organic mulching among all of the parameters. The treatment covered by imperata mulch tended to score the highest compared to other mulches on germination time, seedling height and shoot fresh weight while the minimum yield was recorded in M1 where gliricidia mulch was used. Application of organic mulch displayed better results for most of the parameters than that of the control resulting from an optimal growing environment for areca nut seedlings growth.